The role of K+ channels in uptake and redistribution of potassium in the model plant Arabidopsis thaliana - Sharma, Tripti; Dreyer, Ingo; Riedelsberger, Janin (Frontiers in Plant Science, 2013)
Potassium (K+) is inevitable for plant growth and development. It plays a crucial role in the regulation of enzyme activities, in adjusting the electrical membrane potential and the cellular turgor, in regulating cellular homeostasis and in the stabilization of protein synthesis. Uptake of K+ from the soil and its transport to growing organs is essential for a healthy plant development. Uptake and allocation of K+ are performed by K+ channels and transporters belonging to different protein families. In this review, we summarize the knowledge on the versatile physiological roles of plant K+ channels and their behaviour under stress conditions in the model plant Arabidopsis thaliana.